OPTIMIZATION PROCESS FOR PRODUCTION OF TOMATO LEATHER (Lycopersicum esculentum Mill.) - Askur Rahman; Zainab Zainab; Muhammad Fakhry (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
Research aims to understand the right formula in making tomato leather good and favored.One of the in the form of a fine texture is pectin. Hence in this research using two factors that is pectin and long drying. Design this research using RSM (Response Surface Method) on the software minitab 14.The research results show that pectin had have significant effect on gumminess, hardness, sensory (color and smell) but not had no effect on springiness, chewiness, pH, moisture content, sensory (taste, texture, and preferences a whole) while long drying only had have significant effect on moisture content, color, smell, and texture. The right formula according to the analysis of data using RSM is pectin 1 % and long drying 6,86977 hours.